Amlodipine induces vasodilation via Akt2/Sp1‐activated miR‐21 in smooth muscle cells. (20th May 2019) - Fang, Qin; Tian, Min; Wang, Feng; Zhang, Zhihao; Du, Tingyi; Wang, Wei; Yang, Yong; Li, Xianqing; Chen, Guangzhi; Xiao, Lei; Wei, Haoran; Wang, Yan; et al.
Abstract : Background and Purpose: The calcium antagonist amlodipine exerts important cardioprotective effects by modulating smooth muscle and endothelial functions. However, the mechanisms underlying these effects are incompletely understood. Experimental Approach: Western blotting was used to compare the expression of key genes involved in vascular smooth muscle cell (VSMC) phenotype conversion. Recombinant adeno‐associated virus system was used to regulate miRNA expression in rats via tail vein. Bioinformatics was used to predict the transcriptional regulation of miR‐21 upstream followed by biochemical validation using quantitative real‐time polymerase chain reaction, ChIP‐qPCR and EMSA assays. Key Results: Only the calcium antagonist amlodipine, and no other type of anti‐hypertensive drug, induced miR‐21 overexpression in plasma and aortic vessels in the animal model. Real‐time PCR and luciferase assays showed that amlodipine induced miR‐21 overexpression in vascular smooth muscle cells. Western blot and immunofluorescence assays demonstrated that amlodipine activated Akt2, rather than Akt1, followed by activation of transcription factor Sp1, which regulated VSMC phenotype conversion via binding to the miR‐21 promoter. Furthermore, bioinformatic analyses and luciferase assays demonstrated that amlodipine activated miR‐21 transcription at the ‐2034/‐2027 Sp1‐binding site, which was further demonstrated by ChIP‐qPCR and EMSA assays. Consistently, small‐interfering RNA‐mediated knockdown of Akt2 and Sp1 significantly attenuated the effects of amlodipine on miR‐21 expression in smooth muscle cells. Conclusion and Implications: These results indicate that amlodipine induces smooth muscle cell differentiation via miR‐21, which is regulated by p‐Akt2 and Sp1 nuclear translocation, thereby providing a novel target for cardiovascular diseases.